IMPLEMENTASI PROGRAM KELURAHAN CANTIK KELURAHAN CINTA STATISTIK DI KELURAHAN SUMAHILANG KECAMATAN PEKANBARU KOTA - Listriani, Yuri; Habibie, Dedi Kusuma (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
This study aims to examine the implementation of the Kelurahan Cinta Statistik (Beautiful Village) Program in Sumahilang Village, Pekanbaru City, as part of an effort to build data governance at the village level to support data-driven development and improve the quality of public services. This study used a descriptive qualitative method with the Edward III implementation approach, which encompasses four variables: communication, resources, disposition, and bureaucratic structure. Data were obtained through interviews, observations, and documentation studies. The results indicate that the program has run quite well. There is effective communication between relevant parties, such as the Pekanbaru City Communication and Information Office (Diskominfo) as the village web link provider, the Population and Civil Registration Office (Disdukcapil) as the village data provider, the Pekanbaru City Statistics Agency (BPS) as the Kelurahan Cantik (Beautiful Village) program supervisor, and Sumahilang Village as the implementing agency. Resources from supporting agencies are adequate, and implementers demonstrate high commitment. The program is also strengthened by SOPs and a Circular Letter from the Mayor of Pekanbaru as the legal basis. However, implementation still faces obstacles, such as limited human resources and infrastructure, and limited time due to overlapping agendas with other programs. Therefore, ongoing attention and support from the Pekanbaru City Government is needed to ensure the implementation of the Beautiful Village Program is more optimal and sustainable in the future. Keywords: Beautiful Village Program, Policy Implementation, Sumahilang Village